Pregunta
\[ \text{Find } 2011^2 - 2010^2 \text{?} \]
Ask by Lewis Graham. in South Africa
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
\( 2011^2 - 2010^2 = 4021 \)
Solución
Calculate or simplify the expression \( 2011^2 - 2010^2 \).
Calculate the value by following steps:
- step0: Calculate:
\(2011^{2}-2010^{2}\)
- step1: Calculate:
\(\left(2011+2010\right)\left(2011-2010\right)\)
- step2: Calculate:
\(4021\times 1\)
- step3: Multiply the terms:
\(4021\)
The result of \(2011^2 - 2010^2\) is 4021.
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
The Deep Dive
To solve \( 2011^2 - 2010^2 \), you can utilize the difference of squares formula, which states that \( a^2 - b^2 = (a-b)(a+b) \). Here, let \( a = 2011 \) and \( b = 2010 \). So we have: \[ 2011^2 - 2010^2 = (2011 - 2010)(2011 + 2010) = 1 \cdot (2011 + 2010) = 1 \cdot 4021 = 4021. \] Thus, \( 2011^2 - 2010^2 = 4021 \).
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium